The efficacy of freehand, pilot drilled and fully guided implant surgery in partially edentulous patients: A randomized control trial - Abdulkhaliq Ali F. Alshadidi; Lujain Ibrahim N. Aldosari; Abdullah Hasan A. Alshehri; Rayan Ibrahim H. Binduhayym; Rajamanoj Kondaveeti; Vishwanath Gurumurthy; Sunil Kumar Vaddamanu (PLoS ONE, 2026)
Background Partial edentulism poses challenges to oral function, aesthetics, and quality of life. Implant placement techniques—freehand, pilot-drilled, and fully guided—differ in accuracy, surgical time, and outcomes. In this study, only one predefined index implant per patient was analyzed to avoid confounding from multi-implant cases, and template fabrication for the pilot-drilled group was performed using diagnostic wax-up and thermoplastic material. This study evaluated these techniques in partially edentulous patients. Methods Ninety patients were randomly assigned to three groups: freehand (n = 30), pilot- drilled (n = 30), and fully guided (n = 30). Surgery duration, implant placement accuracy, post- operative complications, early implant failure rates, and patient satisfaction were measured. Accuracy was assessed using standardized CBCT imaging at 12 months, and satisfaction was evaluated via a validated questionnaire six months after prosthetic loading. Results The fully guided technique demonstrated superior accuracy (p < 0.001), shorter surgical times (45 minutes vs. 60 and 75 minutes, p < 0.01), fewer complications (5% vs. 15% and 20%, p < 0.05), and higher satisfaction (9.2/10, p < 0.01). Early implant failure, defined at the implant level, occurred in 4/30 implants (13.3%) in the freehand group, 0/30 in the pilot-drilled group, and 2/30 in the fully guided group (p < 0.05). Conclusion Fully guided implant surgery outperformed other techniques in accuracy, efficiency, and patient satisfaction. These findings support fully guided, prosthetically driven workflows as a preferred option for partially edentulous patients, particularly in cases requiring high precision.